2019
DOI: 10.3389/fcimb.2019.00124
|View full text |Cite
|
Sign up to set email alerts
|

Antigen I/II Participates in the Interactions of Streptococcus suis Serotype 9 With Phagocytes and the Development of Systemic Disease

Abstract: Streptococcus suis is an important porcine bacterial pathogen and a zoonotic agent causing a variety of pathologies including sudden death, septic shock, and meningitis. Though serotype 2 is the most studied serotype due to its presence worldwide, serotype 9 is responsible for the greatest number of porcine cases in Spain, the Netherlands, and Germany. Regardless of its increasing importance, very few studies have investigated S. suis serotype 9 virulence factors and pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Furthermore, exacerbated inflammation is a hallmark of the S . suis -induced systemic infection and is responsible for host death due to septic shock [11, 36]. In accordance, plasmatic levels of the different pro-inflammatory mediators (IL-6, IL-12p70, IFN-γ, CCL2, CCL3, CCL4, CCL5, and CXCL2) were elevated in mice infected with the serotype 9 wild-type strain (Fig 9).…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…Furthermore, exacerbated inflammation is a hallmark of the S . suis -induced systemic infection and is responsible for host death due to septic shock [11, 36]. In accordance, plasmatic levels of the different pro-inflammatory mediators (IL-6, IL-12p70, IFN-γ, CCL2, CCL3, CCL4, CCL5, and CXCL2) were elevated in mice infected with the serotype 9 wild-type strain (Fig 9).…”
Section: Resultsmentioning
confidence: 54%
“…To better explain differences in virulence, and since S . suis systemic infection is associated with persistent bacteremia [11, 36], blood bacterial burden was evaluated 12 h and 24 h post-infection. All mice infected with the wild-type strain presented elevated blood bacterial burdens that averaged 5 x 10 8 CFU/mL (Fig 8B and 8C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results demonstrated that PCV2 cause apoptosis for it induce the chaperonin containing tailless complex polypeptide 1 decrease 59 and supplemented pathways like Wnt/Ca 2+ , and SS2 could binding to cell extracellular secreted protein 60,61 though EMC-receptor interaction. PCV2 caused cell catabolism was greater than anabolic, while SS2 caused a violent cell response.…”
Section: Discussionmentioning
confidence: 71%